Obstacles to Receiving Dental Healthcare Services in Dental Schools from the Viewpoint of Patients: A Qualitative Study - bahareh Tahani; Arman Dayyan (Mashhad University of Medical Sciences, 2024)
Background: Dental schools are responsible for providing high-quality and inexpensive need-based oral health services. The aim of this study was to investigate the barriers associated with receiving dental healthcare services in Isfahan Dental School from the patients' perspective.Methods and Materials: This qualitative research which was conducted from January-October 2022, and included patients who referred to the Oral Medicine Department of Isfahan Dental School in 2019, but did not receive any treatment during the follow-up period until 2021. Participants were recruited through a purposive sampling approach. Semi-structured telephone-based interviews were conducted. The interviews were audio-recorded and carefully transcribed and then each transcript was saved and imported in to MAXQDA software. Truth value, consistency, confirmability, and applicability criteria were assessed to affirm the credibility of data. Obtained data were then encoded using a content analysis approach. Results: A total of 25 patients were interviewed. Five emergent themes and 15 sub-themes were identified: 1) availability (subthemes: not proving care to specific cases and not providing the course in that semester); 2) personal reasons (fear, time restrictions, trust issues); 3) quality (dissatisfaction with the dental treatment and care provider); 4) ability to pay (high tariffs and other financial problems); 5) accessibility (difficulties in scheduling an appointment, long distance, unnecessary bureaucracy, being overly crowded, student-related factors and time-consuming process)Conclusion: Patients mentioned a wide range of barriers to receiving timely and required dental treatments in this dental school. These factors included personal reasons, those related to the care delivery system such as accessibility and quality, and some related to the provision-setting, i.e. the dental school. These insights can help the dental faculty address the obstacles associated with patient admission and referrals in order to enhance patients' experience of receiving dental care in dental schools and increase their overall satisfaction.